Sustainable Economic Development Challenges, Policies, and Reforms - Erokhin, Vasilii; Gao, Tianming; Vasile, Andrei Jean (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a pivotal publication that addresses the contemporary challenges of globalization and elaborate policy responses to environmental pollution, climate change, economic disruptions, poverty, hunger, and other threats to sustainable economic development. Many parts of the world, territories, and societies are now changing at an unprecedented pace in ways that fundamentally affect the markets, people, the environment, and biodiversity. Such changes are primarily driven by rapid social and economic developments, economic disparities between countries, the internationalization of production and value chains, and industrialization. Increasingly frequently, business interests are interfering with sustainable development goals. The issue is how to converge the economic benefits with the urgent need for establishing resilient production chains, social networks, sustainably-operating markets, and environmental protection. This publication highlights the need for the balanced economic development and comprehensive coverage of many sustainability-business areas. Economic, production, financial, and social factors of sustainability are discussed by over 90 contributors representing 40 universities and research institutions from seven countries. Their findings are translated into workable approaches and policies for the benefit of the global economy, people, and the environment.